1637 : the Transylvanian decision - Flint, Eric; Waters, Robert E., 1968- (Ring of fire (Riverdale, N.Y.), 2022)
"Up-timer Morris Roth and his Grand Army of the Sunrise stand at a crossroads. Military success against the Polish-Lithuanian magnates has all but guaranteed a continued push east into Ruthenian lands. There, Roth hopes to further his Anaconda Project so that tens of thousands of Jews are not slaughtered in what's to become known as the Chmielnicki Pogrom of 1648. An envoy from Transylvania arrives with a promising offer from its prince, who wishes to form an alliance with Bohemia, but the land shrouded in the fog of the Carpathian mountains and known only to most up-timers as the playground of Count Dracula is a vassal state of the Ottoman Empire. Such an alliance would surely draw the ire of Sultan Murad IV. The United States of Europe agrees to assist the Bohemian forces, and sends in the Silesian Guard, under the command of Brigadier Jeff Higgins. They also send in Gretchen Richter to organize and lead the political struggle. Transylvania is thrown into political, social, and religious turmoil as battle lines are drawn. Whatever happens and whoever wins the fight, one thing is certain: the history of Eastern Europe will change radically. In fact, it already has"--